Avalia????o das cren??as com rela????o aos idosos e da forma????o na ??rea de envelhecimento dos m??dicos da estrat??gia sa??de da fam??lia do munic??pio de An??polis, GO - Vieira, Aila Davis Fanstone Pina (2016)
The proportion of people aged 60 or older in the world is growing more than any other age group, and it is estimated that Brazil will be the fifth country in the world with the highest number of people in this age group by 2025. This fact brings the need for optimizing health opportunities, which according to the World Health Organization should be done by Primary Care. In Brazil, this level of health care is organized by the Family Health Strategy, with the Family Doctor being the professional responsible for treating most of the country's elderly. This research aimed to evaluate the family doctors in the city of Anapolis as to their training in the field of aging, their basic knowlegde about aging, and their beliefs about old age. It was found that there is a greater insertion of the discipline Geriatry / Gerontology in medical schools in recent years, but this teaching is still focused on the physical aspects of aging, with little concern for the social and psychological aspects. Doctors in the Family Health Strategy are young, and did not participate in research or courses in gerontology. They have little previous experience with elderly and have basic knowledge mainly on the physical aspects of aging, as well as a negative trend in beliefs regarding the elderly. It was concluded that there is need to review the medical training in the field of aging, with a more holistic approach and greater practical experience.